Retinoic Acid Delivery via Ultraflexible Nanovesicular System for the Management of Posterior Segment Ocular Diseases - Gupta, Vandana; Srivastava, Noopur; Verma, Megha; Beohar, Mahima; Verma, Vishal (Scripta Medica, 2026)
Background/Aim: The ongoing perusal centred on formulating and analysing ultraflexible nanovesicular system ie nano-transfersomes for carrying retinoic acid locally to the deeper, posterior regions of the opticMethods: The composition of transfersomes were refined and evaluated by different criteria such as vesicle diameter and distribution, surface charge, encapsulation capacity, surface morphology, viscosity and pH, Additional analyses included drug release behaviour in simulated tear fluid (STF), 3 month stability analysis and ocular safety test using hen’s egg test chorioallantoic membrane (HET-CAM). Results: The ideal blend (F12) showed the median of vesicle diameter 155.32 ± 4.45 nm, scaled by the light scattering process (Malvern Zetasiser, ZEM 5002, UK), The Zeta potential measured approximately -36.5mV, signifying a negative surface charge, which consequently resulted in the absence of particle aggregation. The % entrapment efficiency for the different formulations ranged from 65.45 ± 1.27 to 79.12 ± 2.23. Nano-transfersomes displayed a spherical and elastic morphology, characterised by either unilamellar or multilamellar vesicle structures. The viscosity and pH of retinoic acid loaded nano-transfersomal formulations were measured to be approximately 20.0 ± 2.1 to 48.0 ± 1.8 cP and range of 5.0 ± 0.5 to 7.0 ± 0.1, respectively. The drug release profile in STF was observed to be 98.89 ± 0.45 after 24 h.Conclusion: The drug release profile of retinoic acid loaded ultraflexible nanovesicular system indicating a sustained release pattern. According to storage stability studies, the formulation exhibited greater stability under refrigerated conditions. Research findings suggested that the nano-transfersomal formulation loaded with retinoic acid could provide prolonged release and stable nano transfersome formulation with suitable physico-chemical characteristics facilitating its easy application to the eye. Nano-transfersome might be an innovative approach for delivering retinoic acid to the eye, particularly for treating diseases affecting the posterior segment, due to its distinctive properties such as flexibility, prolonged drug release and reduced size.
Keywords: Tretinoin; Exosomes; ultraflexible nanovesicular system; Posterior eye; Diseases, ocular